The Citrus sinensis peel extract’s increase HDL and reduce LDL levels in cigarette smoke-induced Rats - Ika Setyawati; Armellia Sandra Tamara (Pharmaciana, 2023)
Background: Cigarette smoke contains various oxidative substances that can cause oxidative stress and can cause changes in the lipid profile especially in HDL and LDL. Oxidative stress changes can be inhibited by the administration of antioxidants from sweet orange peel which is expected to improve lipid profile. Objective: to find out the effect of sweet orange extract on changes in HDL and LDL levels.Method: Experimental research with pre and posttest group control design. The subjects were 25 white rats (Rattus novergicus) divided into five groups: negative, positive, dose 1 (37,5 mg / kgBW), dose 2 (75 mg / kgBW) and dose 3 (112,5 mg / KgBW) with each group consisting of 5 rats.Results: Statistic analysis of pretest and posttest HLD and LDL levels showed different mean (p = 0,043) for all groups. The highest difference in HDL levels was in the positive control group (37.55 mg / dL) and the lowest in the negative control group (2.66 mg / dL). The highest difference of LDL level was in positive control group (53,57 mg / dL) and lowest in negative control group (3,26 mg / dL). Conclusion: The results of this study can be concluded that the administration of sweet orange peel extract (Citrus sinensis) can inhibit the decrease in HDL cholesterol and increased levels of LDL in white rats (Rattus novergicus) induced by cigarette smoke.